(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: To summarize evidence on the cost-effectiveness of PD-(L)1 inhibitors as first-line therapy in patients with high PD-L1 expression non-small cell lung cancer. Methods: A systematic review following the PRISMA guidelines was conducted, searching PubMed, Embase, Scopus, and health technology assessment agency websites up to September 24, 2022. Eligible studies evaluated the economic outcomes of PD-(L)1 inhibitors as first-line treatment for high PD-L1 expression non-small cell lung cancer. Study quality was assessed using the CHEERS and QHES checklists Results: 17 eligible studies were included, mostly from high-income countries (HICs), using model-based analyses from healthcare system or third-party payer perspectives. Pembrolizumab was cost-effective compared to chemotherapy in most HICs, except Singapore, but not against pembrolizumab-platinum combinations in Sweden. In China, its cost-effectiveness was uncertain. Cemiplimab was cost-effective compared to pembrolizumab or chemotherapy in the US. Atezolizumab showed inconsistent results depending on willingness-to-pay (WTP) thresholds in the US and China. Drug price significantly impacted cost-effectiveness results. Quality scores ranged from 18–22.5/28 (CHEERS) and 71.5–92.5/100 (QHES). Conclusion: Cost-effectiveness of PD-(L)1 inhibitors for the first-line NSCLC treatment varied by country, comparator, model setting, and WTP. Policymakers should use country- and healthcare system-specific economic evaluation to guide their decision-making on resource allocation.